Colorectal cancer among young native Indonesians: A clinicopathological and molecular assessment on microsatellite instability (Faculty of Medicine Universitas Indonesia, 2010)
Aim: To obtain clinicopathological characteristics of colorectal cancer among young native Indonesians and to assess MLH1, MSH2, and SMAD4 protein expressions, comparing them with a matched population of colorectal cancer patients aged 60 years old and older.Methods: Medical records of colorectal cancer patients aged 40 years or younger and 60 years or older from several hospitals in three Indonesian cities â Jakarta, Makassar, and Bandung - were reviewed. The ânativeâ ethnic groups were selected from those originating from Java, Makassar (South Celebes),Â Minangkabau (West Sumatra). Ethnicity of 121 colorectalÂ carcinoma patients was confirmed by fulfilling requirements in a questionnaire. Tumor specimens of those patients underwent evaluation for histopathology, tumor grading as well asÂ immunohistochemical analysis to assess MLH1, MSH2 protein expressions to detect microsatellite instability mutation pathway and SMAD4 protein expression to reconfirm that the specimens were not microsatellite instability origin.Results: There were 121 colorectal carcinoma cases of Sundanese, Javanese, Macassarese and Minangkabau ethnic group. This study indicated that colorectal cancer has statistically different grade (p = 0.001) between the young and the older patients. Immunohistochemical staining for MSH2 protein and MLH1 were done for 92 and 97 specimens respectively. There was no significant difference between the expressions of MLH1 and MSH2 on tumor grading, indicated there was no correlation between microsatellite instability and tumor grading in this study.Conclusion: Colorectal cancer in young native Indonesian patients (40 years old or less) was not different in clinicopathological characteristics compared to older patients (60 years old or more) in similar ethnic groups. There was also no difference in MSH2 and MLH1 protein expressions, important indicators of microsatellite instability and. (Med J Indones 2010; 19:245-51)Keywords: colorectal cancer, microsatellite instability, MLH1, MSH2, native Indonesian, SMAD4